Ciliated respiratory epithelium encapsulating Pseudomonas brain abscess due to prior trauma. Issue 1 (15th January 2021) - Jena, Nihar Kanta; Khine, Justin; Khosrodad, Nadia; Krishnamoorthy, Geetha
Abstract : Bacterial brain abscesses are typically spread through a haematogenous route. Open head wounds and neurosurgical interventions are uncommon aetiologies. Ectopic tissue found in the cerebral cortex is usually ascribed almost entirely from carcinomas. Here, we describe a 57-year-old gentleman who, 22 years after a fireworks related traumatic injury to the left orbit, presented with headaches and altered behaviour. Imaging revealed an abscess immediately superior to the orbit, whose bacterial aetiology was identified to be Pseudomonas aeruginosa, encapsulated by ciliated respiratory epithelium. This represents a case in which tissue was displaced during the initial trauma or craniofacial reconstructive surgery from the frontal sinus.